Quantum Dynamic Approach of B2N(∓,0) and N2B (∓,0) Clusters Study: A Symmetry Breaking due to the Jahn-Teller Effect - Monajjemi, Majid (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2024)
BN compounds play an important role in the preparation of hyper- thin films, that have received signifcant attention in products. In this article, we investigated the electronic structures of and. Triatomic NBN and BNB have recently been studied using various experimental and calculation approaches, and it is totally agreed that both of them are linear in their ground electronic step. The six ions including B2N (-), B2N (+), B2N (0) , BN2 (-), BN2 (+) and BN2 (0) have been studied and been also compared with one another in terms of several basis sets and predication of the symmetry breaking (SB) subject. Artifactual SB with the v3 vibration is occurred in the trial wave functions of coupled-cluster level, even when Brueckner orbitals of all nitrogen and oxygen atoms are used. In the of and molecules, the unpaired electrons are delocalized, while in the asymmetric, they are localized on either one of the B atoms or N atoms of and , respectively. Structures with (SB),, can be stronger by interaction to the . Hereby, the second-order Jahn-Teller effect allows the unpaired electron to localize on boron atom, rather than being delocalized. Finally, from a statistical thermodynamical analysis, we calculated the thermodynamically stabilities of those six ions.